Germline replacement by blastula cell transplantation in the fish medaka - Li, Mingyou (Sci Rep, 2016)
Primordial germ cell (PGC) specification early in development establishes the germline for reproduction and reproductive technologies. Germline replacement (GR) is a powerful tool for conservation of valuable or endangered animals. GR is achievable by germ cell transplantation into the PGC migration pathway or gonads. Blastula cell transplantation (BCT) can also lead to the chimeric germline containing PGCs of both donor and host origins. It has remained largely unknown whether BCT is able to achieve GR at a high efficiency. Here we report efficient GR by BCT into blastula embryos in the fish medaka (Oryzias latipes). Specifically, dnd depletion completely ablated host PGCs and fertility, and dnd overexpression remarkably boosted PGCs in donor blastulae. BCT between normal donor and host produced a germline transmission rate of ~4%. This rate was enhanced up to ~30% upon PGC boosting in donors. Most importantly, BCT between PGC-boosted donors and PGC-ablated hosts led to more than 90% fertility restoration and 100% GR. Therefore, BCT features an extremely high efficiency of fertility recovery and GR in medaka. This finding makes medaka an ideal model to analyze genetic and physiological donor-host compatibilities for BCT-mediated surrogate production and propagation of endangered lower vertebrates and biodiversity.